Evaluation of Major to Ultra Trace Element Bulk Rock Chemical Analysis of Nanoparticulate Pressed Powder Pellets by LA‐ICP‐MS. Issue 1 (22nd August 2016) - Peters, Daniel; Pettke, Thomas
Abstract : An efficient, clean procedure for the measurement of element mass fractions in bulk rock nanoparticulate pressed powder pellets (PPPs) by 193 nm laser ablation ICP‐MS is presented. Samples were pulverised by wet milling and pelletised with microcrystalline cellulose as a binder, allowing non‐cohesive materials such as quartz or ceramics to be processed. The LA‐ICP‐MS PPP analytical procedure was optimised and evaluated using six different geological reference materials (JP‐1, UB‐N, BCR‐2, GSP‐2, OKUM and MUH‐1), with rigorous procedural blank quantification employing synthetic quartz. Measurement trueness of the procedure was equivalent to that achieved by solution ICP‐MS and LA‐ICP‐MS analysis of glass. The measurement repeatability was as low as 0.5–2% (1 s, n  =   6) and, accordingly, PPP homogeneity could be demonstrated. Calibration based on the reference glasses NIST SRM 610, NIST SRM 612, BCR‐2G and GSD‐1G revealed matrix effects for glass and PPP measurement with NIST SRM 61×; using basalt glasses eliminated this problem. Most significantly, trace elements not commonly measured (flux elements Li, B; chalcophile elements As, Sb, Tl, In, Bi) could be quantified. The PPP‐LA‐ICP‐MS method overcomes common problems and limitations in analytical geochemistry and thus represents an efficient and accurate alternative for bulk rock analysis. Key Points: Clean and efficient analytical procedure that allows the quantification of up to 58 elements, including unconventional geochemical tracers such as B, As, Sb, Tl and Bi. Measurement trueness equal to that of solution ICP‐MS and LA‐ICP‐MS measurement of glass. Elemental fractionation employing NIST SRM 61× glasses as calibrator is observed, the use of basalt glasses (e.g., BCR‐2G, GSD‐1G) eliminates the problem.